1983
DOI: 10.1002/jso.2930240109
|View full text |Cite
|
Sign up to set email alerts
|

Gut‐associated lymphoid tissue and dimethylhydrazine‐induced colorectal carcinoma in the wistar/furth rat

Abstract: Although gut-associated lymphoid tissue in the form of discrete lymphoid patches (LP-GALT) in mammalian intestine in most prominent in the distal ileum, appendix, and, in some species, the cecal appendage, LP-GALT can be found throughout the intestinal tract. LP-GALT appears as single or multiple subepithelial lymphoid follicles covered by a specialized, structurally unique epithelium. In the colon of the Wistar/Furth (W/Fu) rat, LP-GALT appears as aggregates of follicles, or lymphoid patches, that can be dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

1986
1986
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 12 publications
2
17
0
Order By: Relevance
“…High frequency of GALT carcinomas in carcinogen-treated rats was first reported by Deasy et al (30), and later confirmed by various authors (31)(32)(33).…”
Section: High Frequency Of Colonic Galt Carcinomas In Dmh-treated Ratssupporting
confidence: 55%
“…High frequency of GALT carcinomas in carcinogen-treated rats was first reported by Deasy et al (30), and later confirmed by various authors (31)(32)(33).…”
Section: High Frequency Of Colonic Galt Carcinomas In Dmh-treated Ratssupporting
confidence: 55%
“…Recently in 215 DMH-treated SD rats, tumours were found to be 1% serrated adenomas, 8% microtubular adenomas, 3% serrated carcinomas and 3% microtubular carcinomas (19 (20). A similar percentage (62%) was subsequently found in DMH-treated SD rats (21).…”
Section: Serrated Adenomas and Serrated Carcinomasmentioning
confidence: 75%
“…In another experiment with DMH-treated rats, it was found that 37% of colonic neoplasias had a subjacent organized lymphoid nodule (10). These findings strongly suggest that carcinomas in rats evolve not only from conventional adenomas (6) and from serrated adenomas (7), but also from mucosa of gut-associated lymphoid tissue (GALT) (8,9). However, the lesions which give rise to GALT carcinomas remain unidentified.…”
Section: Importantly Highly Differentiated Carcinomas Were Seen To Ementioning
confidence: 92%
“…Years ago, Deasy et al (8) and Rubio et al (9) reported that colonic carcinomas could also evolve in DMH-treated rats from mucosa built with lymphoid aggregates. In another experiment with DMH-treated rats, it was found that 37% of colonic neoplasias had a subjacent organized lymphoid nodule (10).…”
Section: Importantly Highly Differentiated Carcinomas Were Seen To Ementioning
confidence: 99%